(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
Polypyrrole was chemically synthesized by in situ polymerization in the presence of surfactant dopant on cotton denim fabric. Shape and size of the particles are characterized by SEM micrographs. Electrical and thermal conductivity of fabric samples were measured and it was found that electrical conductivity can be increased by increasing the concentration of polypyrrole, but there is no significant relation between electrical and thermal conductivities.